[Co/Ni] multilayers with robust post-annealing performance for spintronics device applications. (5th October 2018) - Gupta, S; Sbiaa, R; Al Bahri, M; Ghosh, A; Piramanayagam, S N; Ranjbar, M; Akerman, J
Abstract: The effect of annealing on the diffusion induced changes in the magnetic and magnetodynamic properties of (Co/Ni) multilayers were investigated. Here, we report, all aspects of post annealing induced effect on perpendicular magnetic anisotropy (PMA), domain morphology, switching mechanism and high frequency magnetization dynamics to understand spin relaxation. (Co/Ni) multilayers of this study exhibited a loop squareness of 95%, a slight drop in saturation magnetization from 650 emu/cc to 620 emu/cc and high magnetic anisotropy ( K u 3 × 10 5 J m −3 ) even after annealing at temperatures as high as 400 °C. Successive domain mapping by magnetic force microscopy revealed characteristics of multi-domains stripe that feature at all stages of annealing except at 500 °C, attributed to the loss of PMA, driven by interfacial diffusion. High frequency broadband ferromagnetic resonance measurements showed little effect of annealing on intrinsic damping parameter ( α = 0.019–0.024) while inhomogeneous linewidth broadening varied without a clear trend. These results are discussed considering crystallographic modifications and it was found that fcc (1 1 1) texture was retained in the samples until 400 °C post annealing. The retention of a high anisotropy, high magnetization and low damping constant after high temperature annealing makes these Co/Ni multilayers suitable for designing spin torque based memory devices.